Multiplex plasmonic anti-counterfeiting security labels based on surface-enhanced Raman scattering - Cui, Yan (2020)
We demonstrate a multiplex plasmonic anti-counterfeiting platform by embedding multiple molecules on a single substrate with superior nanometer scale spectral and spatial resolution. The encoded specific molecular information can be read out only using Raman spectroscopy. Multiplexing increases the complexity of these plasmonic security labels without compromising the spectral resolution.